Culture beats gender? The importance of controlling for identity- and parenting-related risk factors in adolescent psychopathology. (February 2018) - Seiffge-Krenke, Inge; Persike, Malte; Besevegis, Elias; Chau, Cecilia; Karaman, Neslihan Güney; Lannegrand-Willems, Lyda; Lubiewska, Katharzyna; Rohail, Iffat
Abstract: This study analyzed the unique effects of gender and culture on psychopathology in adolescents from seven countries after controlling for factors which might have contributed to variations in psychopathology. In a sample 2259 adolescents ( M = 15 years; 54% female) from France, Germany, Turkey, Greece, Peru, Pakistan, and Poland identity stress, coping with identity stress, maternal parenting (support, psychological control, anxious rearing) and psychopathology (internalizing, externalizing and total symptomatology) were assessed. Due to variations in stress perception, coping style and maternal behavior, these covariates were partialed out before the psychopathology scores were subjected to analyses of variance with gender and country as factors. These analyses leveled out the main effect of country and revealed country-specific gender effects. In four countries, males reported higher internalizing and total symptomatology than females. Partialing out the covariates resulted in a clearer picture of culture-specific and gender-dependent effects on psychopathology, which is helpful in designing interventions. Highlights: Cross-cultural study on psychopathology including adolescents from 7 countries. Variations in the covariates stress perception, coping style and maternal behavior. Controlling for covariates revealed country-specific gender effects. Males ported higher symptomatology than females in 5 countries. The findings are helpful in designing interventions.